Miracles in translation: Lipsius, Our Lady of Halle and two Dutch translations. Issue 1 (February 2015) - Hermans, Theo
<x xml:space="preserve">Abstract</x> In 1604 the Flemish humanist Justus Lipsius (1547–1606) published a Latin treatise on miracles said to have happened on account of the intercession of the Virgin Mary in Halle, a small town near Brussels. There are two Dutch translations of Lipsius' book, one by Albert van Oosterwijck, published in Delft in 1605, the other by Philips Numan, published in Brussels in 1607. The translations are very similar but they are very differently framed. As a result, they are worlds apart, and indeed they were written and printed almost within sight, but on opposite sides, of a shifting military front line dividing the emergent, Calvinist‐dominated Dutch Republic in the north from the Catholic Spanish Netherlands in the south. This article considers the propaganda value of pilgrim sites like Halle and Scherpenheuvel, and explores the two contrasting translations of Lipsius' treatise against the background of the ideological war of words between Reformation and Counter‐Reformation apologists.